Two episodes of regional-scale Precambrian hydrothermal alteration in the eastern Pilbara, Western Australia - Blake, T.; Rothery, E.; Muhling, J.; Drake-Brockman, J.; Sprigg, L.; Ho, S.; Rasmussen, Birger; Fletcher, Ian (Elsevier BV, 2011)
Two regional-scale hydrothermal events have been identified and mapped in the Precambrian rocks of the eastern Pilbara, Western Australia. The first post-dates lithification and tilting of the 2630 ± 6 Ma Carawine Dolomite and pre-dates the 1317 ± 11 Ma Manganese Group. It involved epithermal, mostly silica alteration with subordinate carbonate and minor chlorite and hematite. The most significant result of this event was the development of a regional-scale silica carapace (known as the Pinjian Chert Breccia) on the Carawine Dolomite, ranging from a few metres (?) to about 100 m thick. The second event comprised two phases. The first phase involved regional-scale hematite (±quartz) mineralisation that was broadly synchronous with deposition of the Manganese Group. The second involved regional-scale dissolution of Carawine Dolomite and local precipitation of barite and manganese oxide. It post-dates lithification of the lower part of the Manganese Group and was either synchronous with, or post-dated, deposition of the upper part of the Group.This study highlights the important roles of bedding-parallel aquicludes and unconformities in Precambrian hydrothermal systems, the role of physical and chemical variations in lithologies in controlling the locations of alteration and mineralisation, and shows that ancient crustal fractures acted, repeatedly, as fluid conduits.It also shows that Precambrian hydrothermal events in non-magmatic rocks in non-orogenic settings can be intense and widespread, affecting thousands of square kilometres. Further, by dating such events, links can be made between relatively undeformed sedimentary successions and seemingly unrelated Precambrian orogens. The study also challenges a long-standing, supergene-based model for the formation of silica and manganese in the eastern Pilbara and adds a new component to the Pilbara iron ore story.